2006
DOI: 10.1007/s10552-006-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in anti-inflammatory cytokine signaling and the prevalence of gastric precancerous lesions in Venezuela

Abstract: While the results of the present study suggest roles of genetic variability in these anti-inflammatory mediators in different stages of gastric carcinogenesis, there is high likelihood that they were chance findings due to multiple comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
1
14
1
1
Order By: Relevance
“…The IL-4-590 C>T polymorphism was not associated with either overall or subtype GC. This finding concerning overall GC risk was in agreement with that from studies in Chinese Taiwan (Wu et al, 2003;Lai et al, 2005), Spain (Garcia- Gonzalez et al, 2007), and Venezuela (Kato et al, 2006). Of note, the risk of the polymorphism remained nonsignificant even in a case-control analysis for HP infected patients and controls in a Japanese population (Ando et al, 2009).…”
Section: Gene Polymorphisms and Risk Of Gastric Cancer In A Populatiosupporting
confidence: 89%
See 1 more Smart Citation
“…The IL-4-590 C>T polymorphism was not associated with either overall or subtype GC. This finding concerning overall GC risk was in agreement with that from studies in Chinese Taiwan (Wu et al, 2003;Lai et al, 2005), Spain (Garcia- Gonzalez et al, 2007), and Venezuela (Kato et al, 2006). Of note, the risk of the polymorphism remained nonsignificant even in a case-control analysis for HP infected patients and controls in a Japanese population (Ando et al, 2009).…”
Section: Gene Polymorphisms and Risk Of Gastric Cancer In A Populatiosupporting
confidence: 89%
“…Of note, the risk of the polymorphism remained nonsignificant even in a case-control analysis for HP infected patients and controls in a Japanese population (Ando et al, 2009). We observed that T was a dominant allele in Asian populations (Wu et al, 2003;Lai et al, 2005;Ando et al, 2009), but a minor one in European and African populations (Kato et al, 2006;Garcia-Gonzalez et al, 2007). Despite distinct allele and genotype frequencies, the negative association with GC is, however, consistent among different populations.…”
Section: Gene Polymorphisms and Risk Of Gastric Cancer In A Populatiomentioning
confidence: 59%
“…One study of Venezuelan subjects revealed that those with homozygotes with the low activity allele (GG) of the A398G polymorphism in the IL-4R gene (rs1805010) had a modestly increased risk of gastric atrophy (OR = 1.52, 95% CI = 1.05-2.21) (Kato et al, 2006), suggesting the role of genetic variability in the anti-inflammatory mediators in the genesis of H. pylori-induced gastric precancerous lesions. iNOS C150T (rs2297518) and PRKCH rs3783799 G/A polymorphisms: PRKCH is shown to be involved in oxidative stress, by activating iNOS and nitric oxide production (Pham et al, 2003).…”
Section: Il-4rmentioning
confidence: 99%
“…IL-4 T-590C 5'UTR rs2243250 1,301 Venezuelan (Kato, 2006) TT ,CT :0.82,CC :0.81 IL-4R C-3223T 5'UTR rs2057768 1,301 Venezuelan (Kato, 2006) CC ,CT :0.97,TT :1.01…”
Section: Il-2 T-330gmentioning
confidence: 99%
See 1 more Smart Citation